Pension Funds: Investment Risk Management - Parfonova, L.G.; Bikinina, A.O. (Економічний вісник Донбасу, 2013)
In the article the necessity of the pension system reform was proved. The basic types of pension plans non-governmental pension provision were described. The pension plan which is the most suitable for the modern condition of the Ukrainian pension system was defined. The risks associated with the functioning of the pension system were classified. The main methods of risk management were suggested. У статті обґрунтовано необхідність реформування вітчизняної пенсійної системи. Описано основні види пенсійних планів недержавного пенсійного забезпечення. Визначено пенсійний план, який найбільше підходить для сучасного стану пенсійної системи України. Наведено класифікацію ризиків, пов’язаних з функціонуванням пенсійної системи. Запропоновано основні методи управління ризиками. В статье обоснована необходимость реформирования отечественной пенсионной системы. Описаны основные виды пенсионных планов негосударственного пенсионного обеспечения. Определен пенсионный план, наиболее подходящий для современного состояния пенсионной системы Украины. Приведена классификация рисков, связанных с функционированием пенсионной системы. Предложены основные методы управления рисками.